Choriocapillaris dropout in early age-related macular degeneration - Lutty, Gerard A.; McLeod, D. Scott; Bhutto, Imran A.; Edwards, Malia M.; Seddon, Johanna M. (Experimental eye research, 2020)
Loss of choriocapillaris (CC) in advanced age-related macular degeneration (AMD) is well documented but changes in early AMD have not been quantified. Postmortem eyes from donors with clinically documented early AMD were examined in choroidal whole mounts to determine the area, pattern, and severity of CC loss. Choroids from postmortem human eyes without AMD (n = 7; mean age = 86.1) and from eyes with a Grade 2 clinical classification of early AMD (n = 7; mean age = 87) were immunolabeled with Ulex europaeus agglutinin (UEA) lectin-FITC to stain blood vessels. Whole mounts were imaged using confocal microscopy and image analysis was performed to determine the area of vascular changes and density of vasculature (percent vascular area, %VA). All areas evaluated had a complete RPE monolayer upon gross examination. In age-matched control eyes, the CC had broad lumens and a homogenous pattern of freely interconnecting capillaries. The mean %VA ± standard deviation in submacula of control subjects was 78.1 ± 3.25%. In eyes with early AMD, there was a significant decrease in mean %VA to 60.1 ± 10.4% (p < 0.0001). The paramacular %VA was not significantly different in eyes with or without AMD. The area of submacular choroid affected by CC dropout was 0.04 ± 0.09 mm2 in control eyes. In eyes with early AMD, the mean area affected by CC dropout was significantly increased (10.4 ± 6.1 mm2; p < 0.001). In some cases, incipient neovascular buds were observed at the border of regions with CC dropout in early AMD choroids. In conclusion, UEA lectin-labeled choroidal whole mounts from donors with clinically documented early AMD has provided a unique opportunity to examine regional changes in vascular pathology associated with choriocapillaris. The study demonstrated attenuation of submacular CC in early AMD subjects but no vascular pathology was observed outside the submacular region. While the affected area in some eyes was quite extensive histologically, these changes may not be detectable clinically using standard in vivo imaging. •There is significant loss of submacular choriocapillaris in subjects with early AMD compared to control subjects.•On the contrary, there was no vascular pathology in paramacular choriocapillaris of the AMD subjects.•Attenuation of choriocapillaris was associated with arteriosclerotic and hypertensive changes in Sattler's layer arterioles.•Some of the areas of choriocapillaris loss had early choroidal neovascularization formations.